Software program development of a high-precision magnetometer system for human-occupied vehicles - Q. Zhang; Q. Zhang; K. Zhou; M. Deng; L. Huang; C. Li; Q. Zhang (Geoscientific Instrumentation, Methods and Data Systems)
Cesium optically pumped magnetometers are widely used in geophysical exploration, environmental monitoring, and scientific research for magnetic field measurements. Traditional magnetometer systems, however, encounter limitations in complex environments due to magnetic interference, low data acquisition efficiency, and inadequate real-time control, which affect both application and accuracy. To overcome these challenges, this paper presents a software system designed for cesium optically pumped magnetometers. The system incorporates automatic probe switching, data acquisition, user interface control, and a compensation algorithm. The automatic switching function mitigates dead zones in the optically pumped probes, ensuring continuous data collection. The data acquisition module supports multiple formats and transmission protocols, enhancing efficiency and ensuring data integrity. The user interface facilitates real-time monitoring and control of magnetometer operations. The system employs the Tolles–Lawson model to effectively suppress environmental magnetic interference, ensuring high-precision measurements even in complex environments. Experimental results confirm the system's enhanced sensitivity and stability, making it a reliable tool for precise magnetic field measurements in challenging conditions.